2016
DOI: 10.1038/gt.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an alveolar type I epithelial cell-specific DNA nuclear import sequence for gene delivery

Abstract: The ability to restrict gene delivery and expression to particular cell types is of paramount importance for many types of gene therapy, especially in the lung. The alveolar epithelial type I (ATI) cell, in particular, is an attractive cell type to target, as it comprises 95% of the internal surface area of the lung. We demonstrate, through microinjection of fluorescently labeled plasmids, that a DNA sequence within the rat T1α promoter was able to mediate ATI cell-specific plasmid DNA nuclear import due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Following successful endosomal escape and vector unpacking another significant barrier to gene delivery arises: nucleases present in the cytoplasm can degrade released NAs. For instance, several studies have demonstrated that the half-life of pDNA in the cytoplasm is in the range of 50-90 min [2,5,177]. Surprisingly, research on NA degradation in the cytosol remains rather limited to date, presumably because only few techniques are available to investigate this experimentally.…”
Section: Cytoplasmic Degradationmentioning
confidence: 99%
See 4 more Smart Citations
“…Following successful endosomal escape and vector unpacking another significant barrier to gene delivery arises: nucleases present in the cytoplasm can degrade released NAs. For instance, several studies have demonstrated that the half-life of pDNA in the cytoplasm is in the range of 50-90 min [2,5,177]. Surprisingly, research on NA degradation in the cytosol remains rather limited to date, presumably because only few techniques are available to investigate this experimentally.…”
Section: Cytoplasmic Degradationmentioning
confidence: 99%
“…Gene therapy is defined as the delivery of therapeutic genes to target cells in order to replace or counteract a malfunctioning gene and has emerged as a promising strategy to cure a wide variety of inherited or acquired diseases at their genetic roots [1][2][3][4]. Besides the delivery of pDNA, several other nucleic acids (NAs), such as mRNA, siRNA and miRNA, have emerged as promising tools to modulate protein expression levels [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations